2021
DOI: 10.1063/5.0049357
|View full text |Cite
|
Sign up to set email alerts
|

Multitemperature parameter optimization for fused deposition modeling based on response surface methodology

Abstract: Fused deposition modeling (FDM) is an additive manufacturing technology that is extensively applied in engineering and medicine and offers a wide range of raw materials, low manufacturing cost, and personalized features. The mechanical properties of parts fabricated by FDM are greatly influenced by the multitemperature process parameter system. However, systematic research on the relationship between the multitemperature parameter system and mechanical properties of FDM parts is lacking. In this study, we used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The medium range of filling speeds, high filling density, and thin layer thickness were found to be responsible for the strong interfacial bonding strength 195 . Wang et al 196 used RSM to investigate the effect of varied temperature conditions (the temperatures of the nozzle, platform, and environment) on the tensile strength of CF/PLA composite specimens. The optimal temperature parameters of 231, 80, and 35°C for the nozzle, platform, and environment were predicted, respectively.…”
Section: Fdm 3d Printing Process and Equipment Developmentmentioning
confidence: 99%
“…The medium range of filling speeds, high filling density, and thin layer thickness were found to be responsible for the strong interfacial bonding strength 195 . Wang et al 196 used RSM to investigate the effect of varied temperature conditions (the temperatures of the nozzle, platform, and environment) on the tensile strength of CF/PLA composite specimens. The optimal temperature parameters of 231, 80, and 35°C for the nozzle, platform, and environment were predicted, respectively.…”
Section: Fdm 3d Printing Process and Equipment Developmentmentioning
confidence: 99%
“…In the research conducted by Wang et al [50], RSM was used to optimize a multi-temperature parameter system for FDM by examining the effects of temperature conditions (nozzle, platform and environment temperature) on the tensile strength of carbon fiber/polylactic acid composite specimens using the constructed RSM model. The results showed that the RSM optimization method significantly improved tensile strength with a 3.2% gap compared to FDM results.…”
Section: Response Surfacementioning
confidence: 99%
“…The current issue and full text archive of this journal is available on Emerald Insight at: https://www.emerald.com/insight/1355-2546.htm developed as secondary processes to ameliorate the surface integrity and dimensional accuracy of the printed parts (Hashmi et al, 2023a;Tiwary et al, 2022a). The preprocessing techniques are divided into the optimization of printing machine structure (Chu et al, 2021;Marion et al, 2023;Xu et al, 2022) and feedstock filament (Dontsov et al, 2020;Ginoux et al, 2023;Yan et al, 2023), printing strategy optimization (Afsharkohan et al, 2023;Côt e et al, 2023;Jiang et al, 2022;Wang et al, 2021) including printing path, printing speed, build orientation and layer thicknessand slicing optimization methods (Mosleh et al, 2023;Nayyeri et al, 2022;Vinoth Babu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…, 2023; Jiang et al. , 2022; Wang et al. , 2021) – including printing path, printing speed, build orientation and layer thickness – and slicing optimization methods (Mosleh et al.…”
Section: Introductionmentioning
confidence: 99%